Perlindungan Konsumen terhadap Produk Makanan yang Mengandung Bahan Berbahaya - Apri Amalia; Sindi Sindi; Zarieva Yousif; Malika Ramadhani; Sandi Almirah Putri; Nadia Surati Annisa; Daniel Syahputra (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2026)
The circulation of food products containing hazardous chemical substances remains a serious issue in consumer protection efforts in Indonesia. This condition poses significant risks to public health and indicates that food safety regulations have not yet been fully effective. This study aims to analyze the forms of legal protection for consumers, the liability of business actors for consumer losses, and the role of the Food and Drug Supervisory Agency (BPOM) in supervising and enforcing against the distribution of food products containing hazardous chemical substances. This research employs a normative juridical method with a statutory approach, conducted through a literature review of primary, secondary, and supporting legal materials. The results show that consumer protection is comprehensively regulated by Law Number 8 of 1999 on Consumer Protection, Law Number 18 of 2012 on Food, and relevant BPOM regulations. Business actors are strictly liable for consumer losses and may face civil, administrative, and criminal sanctions. BPOM plays a strategic role in supervision and enforcement; however, it still faces various challenges in practical implementation. Therefore, strengthening supervision, ensuring consistent law enforcement, and increasing legal awareness among business actors and consumers are necessary to achieve effective consumer protection.